Lack of impact moderating movement adaptation when soccer players perform game specific tasks on a third-generation artificial surface without a cushioning underlay - Lozano-Berges, G.; Clansey, A. C.; Casajús, J. A.; Lake, M. J. (Sports Biomechanics, 2021)
The objective of this study was to investigate how the inclusion of a cushioning underlay in a third-generation artificial turf (3G) affects player biomechanics during soccer-specific tasks. Twelve soccer players (9 males/3 females; 22.6 ± 2.3 y) participated in this study. Mechanical impact testing of each 3G surface; without (3G-NCU) and with cushioning underlay (3G-CU) were conducted. Impact force characteristics, joint kinematics and joint kinetics variables were calculated on each surface condition during a sprint 90° cut (90CUT), a sprint 180° cut (180CUT), a drop jump (DROP) and a sprint with quick deceleration (STOP). For all tasks, greater peak resultant force, peak knee extensor moment and peak ankle dorsi-flexion moment were found in 3G-NCU than 3G-CU (p < 0.05). During 90CUT and STOP, loading rates were higher in 3G-NCU than 3G-CU (p < 0.05). During 180CUT, higher hip, knee and ankle ranges of motion were found in 3G-NCU (p < 0.05). These findings showed that the inclusion of cushioning underlay in 3G reduces impact loading forces and lower limb joint loading in soccer players across game-specific tasks. Overall, players were not attempting to reduce higher lower limb impact loading associated with a lack of surface cushioning underlay.